How to Read Like You Mean It - Conway, Kyle (Cultural Dialectics, 2023)
In this candid and concise volume, Kyle Conway, author of The Art of Communication in a Polarized World, considers how we can open ourselves to others and to ideas that scare us by reading difficult texts. Conway argues that because we resist ideas we don't understand, we must embrace confusion as a constitutive part of understanding and meaningful exchange, whether between a reader and a text or between two people. Building on the work of hermeneutics scholar Paul Ricoeur, Conway evaluates the recurring paradox of miscommunication that results in deeper understanding and proposes strategies for reading that will allow individuals to give up the illusion of certainty. In elegant and compelling prose, Conway introduces readers to the idea that it is through uncertainty that we can gain access to new and meaningful worlds-those of texts and other people.